Repeat-mediated genetic and epigenetic changes at the FMR1 locus in the Fragile X-related disorders - Usdin, Karen; Hayward, Bruce E.; Kumari, Daman; Lokanga, Rachel A.; Sciascia, Nicholas; Zhao, Xiao-Nan (Frontiers in Genetics, 2014)
Abstract The Fragile X-related disorders are a group of genetic conditions that include the neurodegenerative disorder, Fragile X-associated tremor and ataxia syndrome (FXTAS), the fertility disorder, Fragile X-associated primary ovarian insufficiency (FXPOI) and the intellectual disability, Fragile X syndrome (FXS). The pathology in all these diseases is related to the number of CGG/CCG-repeats in the 5’ UTR of the FMR1 gene. The repeats are prone to continuous expansion and the increase in repeat number has paradoxical effects on gene expression increasing transcription on mid-sized alleles and decreasing it on longer ones. In some cases the repeats can simultaneously both increase FMR1 mRNA production and decrease the levels of the FMR1 gene product, FMRP. Since FXTAS and FXPOI result from the deleterious consequences of the expression of elevated levels of FMR1 mRNA and FXS is caused by reduced FMRP levels, the clinical picture is turning out to be more complex than once appreciated. Added complications are generated by the fact that increasing repeat numbers make the alleles somatically unstable, generating resulting in individuals sometimes having a complex mixture of different sized alleles. Furthermore, it has become apparent that the eponymous fragile site, once thought to be no more than a useful diagnostic criterion, may have clinical consequences for females who inherit chromosomes that express this site. This review will cover what is currently known about the mechanisms responsible for repeat instability, for the repeat-mediated epigenetic changes that affect expression of the FMR1 gene, and for chromosome fragility. It will also touch on what current and future options are for ameliorating some of these effects.